The Effect of using Virtual Reality Media on the Geometric Skills of Elementary School Students - Ary Kiswanto Kenedi; Atika Ulya Akmal; Ciptro Handrianto; Sugito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This research is motivated by the low geometric abilities of elementary school students. This low geometric ability is caused by teachers needing to use instructional media that can develop elementary school students' geometric abilities. In previous research virtual reality learning media was developed which has been declared feasible to be applied in elementary schools. This virtual reality media needs further study to examine its effect on the geometric abilities of elementary school students. This study sought to analyze how primary school pupils' geometric skills were affected by their use of virtual reality media. In this study, 200 fifth-grade students participated in quasi-experimental research with the quantitative approach. Geometric aptitude questions were utilized as data collection instruments. Prerequisite tests, hypothesis tests, and further tests were performed with data analysis techniques using SPSS 26. According to the study, elementary school children's geometric abilities are impacted by their use of virtual reality media. Teachers might use the implications of this research as a guide to help their kids' geometric skills in elementary school.